The impact of seismic air gun exposure on the haemolymph physiology and nutritional condition of spiny lobster, Jasus edwardsii - Fitzgibbon, Q.; Day, R.; McCauley, Robert; Simon, C.; Semmens, J. (Elsevier, 2017)
There is a critical knowledge gap regarding the impacts of seismic air gun signals on the physiology of adult crustaceans. We conducted four controlled field experiments to examine the impact of seismic acoustic signals on spiny lobster, Jasus edwardsii. Seismic air gun exposure suppressed total haemocyte count (THC) for up to 120. days post-exposure, suggesting a chronic negative impact of immune competency. THC levels after 365. days post-exposure, were elevated two fold, potentially indicating an immune response to infection. Haemolymph refractive index was reduced after 120. days post exposure in one experiment, suggesting a chronic impairment of nutritional condition. There was no effect of air gun exposure on 24 haemolymph biochemical parameters, hepatopancreas index or survival. Collectively these results indicate that the biochemical haematological homeostasis of J. edwardsii is reasonably resilient to seismic acoustic signals, however, air gun exposure may negatively influence the lobster's nutritional condition and immunological capacity.